2007
DOI: 10.1007/s10557-007-6035-1
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin: A Potentially Novel Cardioprotective Agent?

Abstract: This is the first study to demonstrate that necrostatins inhibit myocardial cell death and reduce infarct size, possibly via a mechanism independent of the MPTP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
195
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(210 citation statements)
references
References 24 publications
9
195
0
6
Order By: Relevance
“…The mode of cell death of tubular cells in acute kidney injury (AKI) has been a matter of intense discussion (21,22). Because RIPK3-deficient mice have been shown to be partially protected from IRI-induced tubular necrosis (4, 23) and because Nec-1 phenocopies this effect (21,24,25), it was hypothesized that necroptosis might be the mode of cell death that drives parenchymal cells into necrosis. However, it was not ruled out that tubular cell death might have occurred secondary to some changes outside the tubular compartment: e.g., in RIPK3-dependent organ perfusion, which might be altered also upon Nec-1 treatment if the necroptotic pathway was involved.…”
Section: Resultsmentioning
confidence: 99%
“…The mode of cell death of tubular cells in acute kidney injury (AKI) has been a matter of intense discussion (21,22). Because RIPK3-deficient mice have been shown to be partially protected from IRI-induced tubular necrosis (4, 23) and because Nec-1 phenocopies this effect (21,24,25), it was hypothesized that necroptosis might be the mode of cell death that drives parenchymal cells into necrosis. However, it was not ruled out that tubular cell death might have occurred secondary to some changes outside the tubular compartment: e.g., in RIPK3-dependent organ perfusion, which might be altered also upon Nec-1 treatment if the necroptotic pathway was involved.…”
Section: Resultsmentioning
confidence: 99%
“…Necroptosis shares with necrosis the fact that dying cells display the morphological features of necrosis but not of apoptosis, but is highly regulated by an intracellular protein platform 14, 16. Recent advances have shown that activation of the kinase domain of receptor‐interacting protein1 (RIP1) and the assembly of RIP1/3‐containing signalling complex (termed the necrosome) mediated necroptosis contributes to the pathogenesis in preclinical models of brain 17, 18, heart 19, 20, and kidney 21, 22 I/R injury, which can be protected by using the RIP1 kinase inhibitor necrostatin (Nec)‐1. Meanwhile, the necrosome phosphorylates the mixed lineage kinase domain‐like protein (MLKL), which subsequently results in the rapid, active, and dynamic release of cell damage‐associated molecular patterns (DAMPs) following the loss of plasma membrane integrity and promotes ongoing inflammation and secondary tissue injury 23.…”
Section: Introductionmentioning
confidence: 99%
“…Distinguishing these mechanisms of cell death could be crucial in transplantation as necroptosis is phenotypically similar to necrosis and may play a central role in allograft rejection by enhancing the release of proinflammatory danger molecules and promoting inflammatory injury in the graft. Necroptosis has been implicated in a variety of diseases and necrostatin-1 (Nec-1) treatment has been shown to prevent organ injury in models of cerebral cortex infarction (22), chronic intestinal inflammation (23), ethanol-induced liver injury (24), myocardial infarction (25), ischemia-reperfusion injury in the kidney (26) and heart (27), and renal transplantation (28). Hence, necroptosis may be an important link in transplant rejection (29).…”
Section: Introductionmentioning
confidence: 99%